PSIKOLOGI KEBAHAGIAAN MANUSIA - Fuad, Muskinul (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2015)
For centuries, happiness has been the main issue to be discussed by scholars. In regards to the importance of this theme, this article discusses the meaning of happiness, its components, and how to measure it using philosophical and psychological approaches. To make it more functional and beneficial, it is provided with methods of self-development in achieving the meaning and happiness of life. By studying these aspects, and strengthened with personal experience, psychologist sand counselors are expected to be more effective in performing guidance and counseling activities that their clients under their guidance are able to reach a meaningful and happy life.Â Persoalan kebahagiaan telah menjadi tema utama pembahasan para tokoh selama berabad-abad. Mengingat pentingnya tema ini, tulisan ini akan mencoba menjelaskan makna kebahagiaan, komponen kebahagiaan, dan cara mengukurnya, dengan pendekatan filosofis dan psikologis. Agar lebih fungsional dan bermanfaat, tulisan ini akan dilengkapi dengan uraian tentang metode pengembangan diri dalam meraih makna hidup dan kebahagiaan hidup. Dengan mempelajari aspek-aspek ini, yang kemudian dipadu dengan pengalaman masing-masing di lapangan, para psikolog dan konselor diharapkan akan semakin efektif dalam melakukan kegiatan bimbingan dan konseling, sehingga para klien yang dibimbingnya dapat meraih hidup yang bermakna dan berbahagia.